Two Croatian Localities (2010) - Leutloff-Grandits, Carolin (Array, 2012)
In the paper we introduce the fieldsites and describe kinship and helping relations concentrating on different life stages and point out the extent to which family and kin members help each other and why. We found out that historical social relations matter a great deal, and consequently the paper attemps to integrate a broad historical perspective on the topic. The changes and continuities involved in the transition from socialism to the post-socialist era are at the core of the anayisis.